Systematic Optimization Enables Near-Perfect In Vitro Transformation Efficiencies for Spirodela polyrhiza (Greater Duckweed) - Islam, Tasmia; Ligaba-Osena, Ayalew; Josephs, Eric A (bioRxiv, 2025)
The in vitro transformation of plants, or the delivery of foreign genetic material that is incorporated into their genomes, represents a powerful tool both for elucidating genotype-phenotype relationships and for generating plant cultivars which have desirable traits for agriculture and/or biotechnological applications. However, outside of a few model species, the processes involved in transformation are often inefficient and can take months to perform for many plant species, with several bottlenecks occurring at the different stages of calli induction, genetic transfection, and plant regeneration. While duckweeds - aquatic monocots whose species include some of the smallest and fastest-growing flowering plants on the planet - have distinguished themselves with several emerging biotechnological applications, they too are the subject of conflicting reports regarding their transformation potential and ability to be genetically manipulated. Here, we synthesized and optimized the protocols for in vitro transformation of duckweed (Greater Duckweed) from start-to-finish: achieving >90% - 100% efficiencies for each of calli induction; transient and stable genetic transformation; visual marker-free selection of transformants; and regeneration of genetically modified plants with stable transgene expression for over 100 generations - and which in can be achieved over the course of weeks instead of months. The integrated, streamlined approaches for all stages of in vitro transformation overcome many bottlenecks and can help to pave the way for high-throughput functional genomics studies and synthetic biology applications in this biotechnologically-important species.